2011
DOI: 10.1021/ja2053539
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Tetrabutylammonium Graphite Intercalation Compound

Abstract: The intercalation of tetrabutylammonium (TBA) cations into graphite by cation exchange from a sodium-ethylenediamine graphite intercalation compound yields a single-phase first-stage product, C(44)TBA, with a gallery expansion of 0.47 nm. The gallery dimension requires an anisotropic "flattened" cation conformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
76
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 36 publications
11
76
0
Order By: Relevance
“…By conducting extensive X-ray powder diffraction analysis (XRD), they concluded that the intercalation of tetrabutylammonium (TBA) cations into graphite yields a single-phase first-stage product, C 44 TBA, with a gallery expansion of 0.47 nm. Since the freestanding TBA cations have much larger ionic size (0.89 nm), the smaller reported inter-layer distances necessitate an anisotropic ''flattened'' cation conformation [52]. Such ionic conformational flexibilities possibly apply less deformation stress to the graphitic layers at the edges and vertices, generating a more uniform exfoliation pattern on the iso-molded graphite rod, as shown macroscopically also by Fig.…”
Section: Products Characterizationmentioning
confidence: 83%
See 1 more Smart Citation
“…By conducting extensive X-ray powder diffraction analysis (XRD), they concluded that the intercalation of tetrabutylammonium (TBA) cations into graphite yields a single-phase first-stage product, C 44 TBA, with a gallery expansion of 0.47 nm. Since the freestanding TBA cations have much larger ionic size (0.89 nm), the smaller reported inter-layer distances necessitate an anisotropic ''flattened'' cation conformation [52]. Such ionic conformational flexibilities possibly apply less deformation stress to the graphitic layers at the edges and vertices, generating a more uniform exfoliation pattern on the iso-molded graphite rod, as shown macroscopically also by Fig.…”
Section: Products Characterizationmentioning
confidence: 83%
“…This could be best described by the flexibility of the alkyl/aryl groups in the organic quaternary ammonium cations to flatten between the graphene sheets as put forward by Sirisaksoontorn et al recently [52]. By conducting extensive X-ray powder diffraction analysis (XRD), they concluded that the intercalation of tetrabutylammonium (TBA) cations into graphite yields a single-phase first-stage product, C 44 TBA, with a gallery expansion of 0.47 nm.…”
Section: Products Characterizationmentioning
confidence: 99%
“…In the specific case of graphite, this can result in the formation of graphite intercalation complexes (GICs) [1][2][3][4][5][6][7][8][9][10][11][12][13] and in the case of tetraalkylammonium (R 4 N + ) reduction at graphite cathodes, has been found to be accompanied by a significant irreversible volumetric expansion of the host graphite [14][15][16], irrespective of whether intercalation is electrochemical [17,18] or non-electrochemical [16,19]. Various chemical routes to R 4 N + and alkali metal GIC syntheses have been presented [16,[20][21][22] often taking place via cationic displacement reactions. Electrochemical procedures, on the other hand, are less common [23,24], despite the relative simplicity of cathodically charging a graphite electrode in the presence of a R 4 N + -containing electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the formation of expanded graphite through the cathodic intercalation of tetra-alkylammonium ions was reported in the 1970s, although the possibility of graphene formation was not considered in the "pre-graphene" era [45,46]. More recently, a detailed study of chemical intercalation compounds derived from tetra-alkylammonium ions has been reported [47]. Returning to electrochemistry, cationic intercalation has been performed in a single step using the pyrrolidinium cation of a room temperature IL: the product was less than five layers thick, as judged by Raman spectroscopy and transmission electron microscopy, with a low oxygen content [48].…”
Section: Top-down Fabrication Of Graphenementioning
confidence: 99%